Workshop Personal Branding di Era Digital untuk Kompetensi Siswa Sekolah Menengah Kejuruan - Alfarizzi, Rizzal; Fanaqi, Chotijah (Prima Abdika: Jurnal Pengabdian Masyarakat, 2025)
In this increasingly competitive era, many vocational high school graduates find that their jobs don't always align with their chosen majors in school. This can create confusion and hinder career development. The personal branding workshop in the digital era was conducted to fill the knowledge gap about basic personal branding concepts and development strategies on digital platforms, which has become an urgent need for young people in facing increasingly dynamic competition challenges. This workshop uses an interactive lecture method with question-and-answer sessions between presenters and participants. The material covered includes basic concepts of personal branding, self-image development on digital platforms, and ethics in digital platforms. Post-test results show that the workshop provided profound insights and significant benefits for participants. They not only gained theoretical understanding but also practical ways to use digital platforms to enhance their reputation. The workshop successfully encouraged students to think critically about their digital presence, recognize the impact of content on career opportunities, and develop authentic, consistent, and professional personal branding strategies. Overall, participants demonstrated a good understanding of personal branding concepts in the digital era, showing the workshop's effectiveness in achieving its educational objectives.